A late Quaternary record of seasonal sea surface temperatures off southern Africa. (1st September 2017) - Loftus, E.; Sealy, J.; Leng, M.J.; Lee-Thorp, J.A.
Abstract: The southern Cape coastal region is important for understanding both the behavioural history of modern humans, and regional and global climate dynamics, because it boasts a long archaeological record and occupies a key geographical location near the intersection of two major oceans. The western boundary Agulhas Current, implicated in global heat exchange dynamics, is an important modulator of southern African climates and yet we understand its past behaviour only broadly as the Current itself scours the coastal shelf and marine sediment core records necessarily provide little detail. Numerous archaeological sites from both the late Pleistocene and Holocene provide the opportunity for reconstruction of near-shore seasonal SST records, which respond both to localized wind-driven upwellings and Agulhas temperature shifts, corresponding in turn with terrestrial precipitation trends in the near-coastal and summer rainfall regions. Here we present a record of seasonal SSTs extending over MIS5, MIS4, and the Holocene, from serial δ 18 O measurements of a single gastropod species, Turbo sarmaticus . The results show that mean SST shifts accord well with global SST trends, although they are larger than those recorded in the Agulhas Current from coarser-scale marine sediment records. Comparison with a record of Antarctic sea-ice suggests that annual SST amplitude responds to Antarctic sea-ice extent, reflecting the positioning of the regional wind systems that drive upwelling dynamics along the coast. Thus, near-shore SST seasonality reflects the relative dominance of the westerly and easterly wind systems. These data provide a new climate archive for an important but understudied climate system. Highlights: Archaeological seashells provide a record of seasonal SSTs since Last Interglacial. Mean SSTs increase by c. 4 °C across Holocene and decrease by c. 2.5 °C across MIS5/4. Wind-induced upwelling drives shifts in seasonal SST amplitude between c. 3–7 °C. Upwelling dynamics correspond with terrestrial precipitation and Antarctic sea-ice. Proxy links marine and terrestrial seasonal climate systems.